(untitled) (Research, Society and Development, 2021)
The hydrothermal synthesis of MCM-22 zeolite was investigated in reaction systems with different proportions of sodium and potassium cations. The potassium content R, defined as the molar ratio between potassium and the total inorganic cations amounts in the synthesis mixture, varied from 0 to 0.9, keeping constant the cationic concentration and the alkalinity of the system. The materials were characterized by X-ray diffraction (XRD), N2 adsorption/desorption and scanning electron microscopy (SEM). The K+ ions favored the formation of MCM-22 when 45% of sodium was replaced by potassium, reducing the time required to synthesize the MCM-22(P) precursor and producing more crystalline samples. Furthermore, the relative amounts of Na+ and K+ ions remarkably affected the morphology and particle size of the samples. The use of higher potassium contents (R = 0.68 – 0.9) hindered the crystallization of MCM-22 zeolite. Thus, the use of reaction mixtures with adequate proportions of Na+ and K+ can be an effective strategy to produce highly crystalline samples in shorter times, reducing the cost of synthesis of such zeolite